Risk factors for the failure to achieve normal albumin serum levels after albumin transfusion in neonates - Nadya Arafuri; Pudjo Hagung Widjajanto; Ekawaty L. Haksari (Paediatrica Indonesiana, 2016)
Background Albumin transfusion for the treatment of neonatal hypoalbuminemia may reduce morbidity. In conditions with disrupted endothelial integrity (e.g., sepsis and critical illness), the administered albumin may leak into the interstitial space, hence, serum albumin levels may fall below expected levels after transfusion. To date, few studies have been done to evaluate the risk factors for failure to achieve normal neonatal albumin levels after transfusion.Objectives To determine the risk factors for failure to achieve normal neonatal albumin levels after transfusion.Methods We performed a case-control study in the Neonatal Ward of Dr. Sardjito Hospital from 2007 to 2012. Normal albumin level was defined as above 3 g/dL. The case group included neonates with post-transfusion albumin levels <3 g/dL and the control group included those with post-transfusion albumin â‰¥3 g/dL. Subjects received intravenous transfusions of 25% or 20% albumin according to the clinical standard of the Neonatal Ward of Dr. Sardjito Hospital. Neonates with very low birth weight, severe birth trauma, burn injuries, severe bleeding, or incomplete medical records were excluded. The data were analyzed with logistic regression test.Results From January 2007 to December 2012, 124 neonates were enrolled in the study. Multivariate analysis showed that low albumin levels before transfusion (OR 12.27; 95%CI 2.17 to 69.30), presence of critical illness (OR 4.01; 95%CI 1.49 to 10.79), diagnosis of sepsis (OR 3.56; 95%CI 1.36 to 9.32), and the >24-hour interval between albumin examination and transfusion (OR 0.06; 95%CI 0.01 to 0.37) were significant risk factors affecting the failure to achieve normal albumin levels.Conclusions Failure to achieve normal albumin levels after transfusion in neonates was significantly associated with low albumin level prior to transfusion, critical illness, sepsis, and >24-hour interval between transfusion and post-transfusion albumin examination.[Paediatr Indones. 2016;56:129-33.].